Medium-sized foreign-owned German enterprises heavily involved in R&D - Heike Belitz; Alexander Eickelpasch (DIW Economic Bulletin, 2016)
In Germany, the share of private investment in research and development (R&D) by foreign-owned companies from the beginning of the millennium to 2011 remained virtually unchanged at around one-quarter. From 2011 to 2013, this share fell slightly, and for the first time since the mid-1990s also the absolute amount decreased. Growth in domestic firms, however, was so high that there was an increase in the overall R&D of firms in Germany. The decline in investment by foreign companies is likely to reflect strategic decisions in some major enterprises; medium-sized foreign companies have in fact expanded their R&D activities. In the present study, no evidence was found that Germany has become less attractive as a location for research.
Keywords: D24; F21; L60; O31; 330; research and development; manufacturing; foreign direct investment; productivity